ANALYSIS OF INCREASING THE IMPORTANT ROLE OF THE MEDAN STATE MUSEUM IN TOURISM ARCHITECTURE THROUGH A SURVEY BASIS - Lesina Br Manurung; Fajar Ompusunggu (Bulletin of Engineering Science, Technology and Industry, 2024)
State Museum of Medan is an art and cultural museum located in the city of Medan, North Sumatra. The museum was originally established as a Memorial Room in 1971 and was transformed into a North Sumatra Provincial Museum in 1980. On June 1, 1982, the museum officially became the Field Negri Museum. In addition, the museum has an important role in the field of tourism as an educational tourist destination that attracts local and foreign tourists. As a museum of art and culture, the museum not only offers a collection of valuable art and artifacts, but also plays an important role in spreading the cultural heritage of the region to tourists. The Negri Museum of Medan is also an attractive educational center for local and foreign communities who want to deepen their knowledge of the region's history and culture. With this museum, tourists can experience and learn about the rich Malay and Batak art and culture as well as appreciate the uniqueness and beauty of traditional architecture.